Environmental change impacts on carbon and nitrogen dynamics in soils and vegetation: from global synthesis to local case studies - Rocci, Katherine, author; Cotrufo, M. Francesca, advisor; Baron, Jill S., committee member; Knapp, Alan K., committee member; Lavallee, Jocelyn M., committee member (Colorado State University. Libraries, 2022)
Human-induced changes in the Earth system, known collectively as global environmental changes, are modifying terrestrial ecosystems. Feedbacks between land biogeochemistry (e.g., the cycling of elements) and global change are one of the key uncertainties in global climate models, and thus understanding land (e.g., soils and plants) responses to global change will help us predict future climate. In order to advance understating of how soils and plants respond to global changes, we need to work across scales by synthesizing global findings, using experimental networks, and studying context dependent responses at individual sites. Specifically, this dissertation uses this framework to investigate: (1) the responses of carbon (C) in total soil organic matter (SOM) and its fractions to warming, elevated atmospheric carbon dioxide (CO2), altered precipitation regimes, and nitrogen (N) fertilization globally using meta-analysis; (2) SOM C and N stoichiometry and distribution in response to nutrient fertilization in globally-distributed grasslands; (3) plant and soil biogeochemical responses to increased precipitation at a mesic grassland; (4) bulk (wet and dry) N deposition in response to proximity to the road in a topographically complex, subalpine forest. Soil organic matter stores carbon (C) and N and thus helps to control climate and provide energy and nutrients for ecosystem function. Thus, understanding SOM responses to global change will help determine future climate and ecosystem processes. However, SOM is made up of a diverse pool of molecules, and separating SOM into more homogenous functional pools (e.g., particulate and mineral-associated organic matter [POM and MAOM]) can provide clearer understanding of SOM responses to perturbations. By synthesizing global-scale understanding, Chapter 2 showed that POM and MAOM C responded differently to global changes and these responses depended on experiment length, soil depth, and experiment methodology. By investigating how SOM responses to global change varied across a global distribution of grasslands, Chapter 3 found that addition of macro- and micronutrients modified POM and MAOM C:N, depending on ambient environmental conditions, and consistently reduced SOM C stability. By investigating C and N cycling under altered precipitation at a local scale, Chapter 4 showed that studying SOM fractions provided clearer understanding of the mechanisms underlying grassland biogeochemical responses to increased precipitation. Chapters 2-4 all show the value of investigating soil fractions rather than solely the total SOM pool, as studying these fractions provided unique information and greater functional understanding. Global changes are not felt equally by all ecosystems. Ecosystems near sources of N deposition may be especially vulnerable to this global change. The fifth chapter of this dissertation, like the fourth chapter, focused on understanding local responses to global change. The vast majority of roadside N deposition studies find increased N deposition adjacent to roadways, but we did not find this, potentially due to the complex topography at our site or insufficient vehicle emissions. This suggests higher roadside N deposition cannot be assumed for all ecosystems. Altogether this dissertation synthesized and advanced our understanding of global change effects on plant and soil C and N pools and cycling.